ANALISIS BUDAYA ORGANISASI DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA MELALUI MOTIVASI - Bambang Sudarsono (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
This study aims to explain the influence of organizational culture and organizational commitment on motivation and job satisfaction in Semarang State Polytechnic . The aim of this research model examines the effect of organizational culture on motivation, organizational commitment on motivation, organizational culture on job satisfaction, organizational commitment on job satisfaction, job satisfaction and motivation.The population is all Semarang State Polytechnic lecturer who totaled 352 employees. Sample selection techniques using purposive sampling with a sample of 100 people examined. The method used in data collection questionnaire (questionnaire) were given to the respondents. Tests on the research done by the test instrument validity (factor analysis) and the coefficient alpha reliability test, statistical test equipment being used is multiple regression analysis, the R2 test and t-test to test the significance of regression coefficients were generated and mediation test to prove motivation as mediating variables.The results showed that organizational culture and organizational commitment in a positive and significant effect on the motivation of Semarang State Polytechnic lecturer, organizational culture, organizational commitment and motivation in a positive and significant effect on job satisfaction Semarang State Polytechnic lecturer. The results of the study also proves that the variable of organizational commitment has a dominant influence on the increased motivation and job satisfaction. Mediation test results prove that motivation does not mediate the influence of organizational culture and organizational commitment on job satisfaction.